Mechanical Assemblies Design Of Underwater Electric Motor. - Che Maideen, Normariah; Almanar, Indra Putra; Ali, Amir Yazid; Ishak, Dahaman; Arshad, Mohd Rizal (2008)
Electric motor plays an important role in providing Autonomous Underwater Vehicle (AUV) system the capability for motion.